2006
DOI: 10.1016/j.physletb.2006.09.068
|View full text |Cite
|
Sign up to set email alerts
|

Gauss–Bonnet braneworld and WMAP three year results

Abstract: We compare predictions for the spectral index and tensor-scalar ratio in models of patch inflation with the WMAP three year data. There are three cases of these models of inflation, which arise in the Gauss-Bonnet braneworld scenario: Gauss-Bonnet (GB), Randall-Sundrum (RS), and 4D general relativity (GR). We consider the large-field potential V ∝ φ p in both commutative and noncommutative spacetimes, and find that in the cases of the GB and GR patch cosmologies, the quadratic potential is observationally favo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…The RS braneworld was compared against WMAP3 [61,62] and WMAP5 data [63]: the potentials with small-field variations turned out to be favored [62] and the quartic potential excluded [61]. The quartic potential was also excluded in the GB braneworld by WMAP3 data [61]. Planck data were recently used also in [64], but on a DGP brane model different from the present ones.…”
Section: Likelihood Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…The RS braneworld was compared against WMAP3 [61,62] and WMAP5 data [63]: the potentials with small-field variations turned out to be favored [62] and the quartic potential excluded [61]. The quartic potential was also excluded in the GB braneworld by WMAP3 data [61]. Planck data were recently used also in [64], but on a DGP brane model different from the present ones.…”
Section: Likelihood Analysismentioning
confidence: 92%
“…Planck data were recently used also in [64], but on a DGP brane model different from the present ones. Reference [61] also studied non-commutative inflation in the IR limit, using the patch formalism of [40] and WMAP3 data, which led to the exclusion of quadratic and quartic potentials in the σ = 6 model. These potentials have been ruled out also by Planck data, but only in the UV mild non-commutative regime [65].…”
Section: Likelihood Analysismentioning
confidence: 99%
“…For modes with a wavelength much larger than the horizon (k ≪ aH), where k is the comoving wave number. The scalar q-spectral index is given by [22], and in our case becomes…”
Section: Perturbation Spectral From Intermediate Inflation In Patmentioning
confidence: 99%
“…This kind of theory has been applied to possible resolution of the initial singularity problem [13], to the study of Black-Hole solutions [14], accelerated cosmological solutions [15], among others (see Refs. [16][17][18][19][20][21][22]). In particular, very recently, it has been found that for a dark energy model the GB interaction in four dimensions with a dynamical dilatonic scalar field coupling leads to a solution of the form a = exp At f [23], where the universe starts evolving with a decelerated exponential expansion.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, all versions of string theory (except type II) in 10 dimensions include this term. Therefore, it could be interesting to make study the effects of the Gauss-Bonnet term on inflationary brane world models [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%